Comparative evaluation of immune response to secondary inoculation of sheep red blood cells in egg-type chicken - SAINI, SAMITA; CHAUDHARY, M L; BRAH, G S; BAJWA, I S (The Indian Journal of Animal Sciences, 2013)
Present study was conducted to evaluate humoral immune response of 3 White Leghorn (WL) and 2 Rhode Island Red (RIR) strains to booster inoculation of sheep red blood cells. Immune response to sheep red blood cells was measured as total, Mercapto-ethanol resistant (MER) and Mercapto-ethanol sensitive (MES) titre at 6, 10, 14 and 18 days post secondary (booster) inoculation. Haemagglutination titre gives indication of total antibodies while MER and MES titre represented level of immunoglobulin G (IgG) and immunoglobulin M (IgM) respectively. The overall antibody production was higher after booster inoculation when compared with birds not given booster. There were significant differences between the strains for response to booster, with WL being superior and differing significantly from RIR strains. Thus RIR strains had lower level of antibodies against SRBC booster. Of WL selected strains PL1 had better immune responsiveness compared to PL2 and control except for MER level, which was higher in PL2. The overall peak titer value was occurring during 6d PSI for total and MES titre and during 10d PSI for MER titre. The antibody titre after booster inoculation first peaked during 6–10d PSI and then gradually declined. There were significant differences between days PSI for total antibody titre in birds given and not given booster inoculation while MER and MES have no significant differences for days PSI.